PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU YANG DIMODERASI OLEH IKLIM RGANISASI PADA MI SEKECAMATAN WINONG KABUPATEN PATI (Studi Kasus pada Guru-guru Mi Sekecamatan Winong Kabupaten Pati) - ., Shodiqin; Srimindarti, Ceacilia (Proceeding SENDI_U, 2015)
This study aimed to examine the effect of competence and organizational commitment toward teachersâperformance in MI Sekecamatan Winong Pati regency moderated with the organization climate. Thespecific objective of this study was to examine the effect of competence and organizational commitmenttoward teachersâ performances are moderated by the organization climate. The usefulness of this study isto clarify and extend previous research on the effects of competences and organizational commitmenttoward teachersâ performance are moderated organization climate. This study used a population ofteachers in MI Sekecamatan Winong Pati regency much as 107 teachers. Sampling techniques in thisstudy is proportional random sampling methode. The method used in this research is regression withinteraction quasi moderation. Based on the results of the study can be summarized as follows competencehas no effect toward teachersâ performance, organizational commitment effect toward the teachersâperformance, the organization climate no affect the teachersâ performance, the influence of competencetoward teachersâ performance is not moderated by organizations climate, and organizations climatedebilitates the effect of organizational commitment toward teachersâ performance.Keywords : competence, organizational commitment, organization climate, teachersâ performance